Acclimation in plants – the Green Hub consortium. (31st January 2021) - Kleine, Tatjana; Nägele, Thomas; Neuhaus, H. Ekkehard; Schmitz‐Linneweber, Christian; Fernie, Alisdair R.; Geigenberger, Peter; Grimm, Bernhard; Kaufmann, Kerstin; Klipp, Edda; Meurer, Jörg; Möhlmann, Torsten; Mühlhaus, Timo; et al.
Summary: Acclimation is the capacity to adapt to environmental changes within the lifetime of an individual. This ability allows plants to cope with the continuous variation in ambient conditions to which they are exposed as sessile organisms. Because environmental changes and extremes are becoming even more pronounced due to the current period of climate change, enhancing the efficacy of plant acclimation is a promising strategy for mitigating the consequences of global warming on crop yields. At the cellular level, the chloroplast plays a central role in many acclimation responses, acting both as a sensor of environmental change and as a target of cellular acclimation responses. In this Perspective article, we outline the activities of the Green Hub consortium funded by the German Science Foundation. The main aim of this research collaboration is to understand and strategically modify the cellular networks that mediate plant acclimation to adverse environments, employing Arabidopsis, tobacco ( Nicotiana tabacum ) and Chlamydomonas as model organisms. These efforts will contribute to 'smart breeding' methods designed to create crop plants with improved acclimation properties. To this end, the model oilseed crop Camelina sativa is being used to test modulators of acclimation for their potential to enhance crop yield under adverse environmental conditions. Here we highlight the current state of research on the role of gene expression, metabolism and signalling in acclimation, with a focus on chloroplast‐related processes. In addition, further approaches to uncovering acclimation mechanisms derived from systems and computational biology, as well as adaptive laboratory evolution with photosynthetic microbes, are highlighted. Significance Statement: Acclimation allows plants to adapt at the physiological level to changes in their environment, and is pivotal to plant fitness, especially in the light of global warming. The Green Hub consortium aims to understand and enhance the protective effects of the cellular networks that mediate acclimation of plants including crops.